2009
DOI: 10.4067/s0716-078x2009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de distribución espacial de ensambles de macroinvertebrados bentónicos de un sistema fluvial Andino Patagónico

Abstract: RESUMENEn enero de 2006 se estudiaron los patrones espaciales de distribución de comunidades de macroinvertebrados bentónicos de la cuenca hidrográfica del río Baker (45º50' O y 47º55' S) y los principales factores controladores, intentando cubrir la mayor variedad de ecosistemas lóticos. Para llevar a cabo el estudio se seleccionaron 27 estaciones de muestreo ubicadas en las diferentes subcuencas del río. En cada estación se realizó una caracterización fisicoquímica del agua (conductividad, oxígeno disuelto, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
(18 reference statements)
6
16
1
5
Order By: Relevance
“…Esto puede explicarse a partir de que estas plantas generan una mayor disponibilidad de recursos tanto alimenticio como de refugio (Esteves, 1998;Flory & Milner, 1999;Moya et al, 2009). Conjuntamente con el aumento en la abundancia CUADRO 6 Coeficiente de correlación de Kendall no paramétrico entre las variables químicas del agua de estos macroinvertebrados, se incrementó la abundancia de Hydrobiosidae y Glossiphonidae, ambos considerados depredadores.…”
Section: Discusionunclassified
“…Esto puede explicarse a partir de que estas plantas generan una mayor disponibilidad de recursos tanto alimenticio como de refugio (Esteves, 1998;Flory & Milner, 1999;Moya et al, 2009). Conjuntamente con el aumento en la abundancia CUADRO 6 Coeficiente de correlación de Kendall no paramétrico entre las variables químicas del agua de estos macroinvertebrados, se incrementó la abundancia de Hydrobiosidae y Glossiphonidae, ambos considerados depredadores.…”
Section: Discusionunclassified
“…The area is characterized by a remarkable, permanent salinity minimum caused by high discharge of river fluxes. One of the largest rivers of southern Chile in terms of volume is the Baker River basin, 26 726 km 2 (Moya et al 2009). It has a nival regimen with maximum freshwater discharge during the austral summer, when ice melting takes place (river flux around 100-250 m 3 s −1 , Dávila et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The highest values were recorded in winter at stations 3 and 4 (Table 5). (Moya et al 2009b). It may even be compared to a basin which is four times larger, the Damas River basin covering 51,400 ha, where 14 stations were sampled (Figueroa et al 2003), showed the same number of taxa as was recorded in the Boroa basin.…”
Section: Index Bioticmentioning
confidence: 99%
“…In the south-central zone of Chile (36°S to 47°S), studies of macroinvertebrates have been carried out in several regions: Biobío (Habit et al 1998, Valdovinos 2001, Moya et al 2009a, Araucanía (Leiva 2004), Los Ríos (GuevaraCardona et al 2006), and Carlos Ibañez del Campo (Mercado & Elliott 2006, Oyanedel et al 2008, Moya et al 2009b; the majority of which only analyzed the structure of the ensemble of macroinvertebrates.…”
Section: Introductionmentioning
confidence: 99%